Pedagogical networks materialized as teachers' narratives - Carrasco Castilho, Janaina; Auxiliadora Bueno Andrade Megid, Maria (Revista Diálogo Educacional, 2021)
The purpose of this article is to present an analysis of a network of partners and teacher support based on the narratives about pedagogical practices made by teachers at a public school during the year of 2018. It is part of a broader doctorate research that, based on a case study, investigated the collaboration relationships of an Elementary I municipal public school in the countryside of São Paulo. As methodological procedures, a bibliographical study about the social organization in networks was carried out, as well as a field research that followed up on ten teachers acting in professional settings. Narrative interviews were conducted to discuss the pedagogical practices that took place in that school. The analysis was performed from thematic axles extracted from the elements provided by the narratives, which supported the connections with the bibliographical study. The results reached through the analysis of the narratives about such pedagogical practices show the articulation between teachers and partners that belong to different social spaces and times, with whom connections are built through their experiences, not only those inside the school but also those beyond professional settings. Based on the evidences, it was possible to consider that the different interlocutors that comprise a teacher's network - with whom the teacher establishes an exchange relationship boosted by technological means of communication - are responsible for promoting the continuity of the teacher professional education.